The Effect of Project Communications Management on Project Time Performance - Nixon Augustinus Manuputty; Afrizal Nursin (POLITEKNIK NEGERI JAKARTA, 2023)
The construction industry plays a significant role in the country, while project delays cause various problems. Regarding that, communication is very influential on the project performance, especially time performance. This study aims to identify the factors that affect project communications, identify the effect of project communications management on project time performance, and analyze project communications management strategies for improving time performance. The calculation of the Relative Importance Index was carried out to determine the factors that affect project communications. Meanwhile, a simple linear regression analysis was carried out to find out the magnitude of the effect of project communications management on project time performance. The project communications management strategy was obtained by mapping stakeholders using the power/interest grid method. The data was collected based on observations and the results of questionnaires filled out by 38 respondents, consisting of the owner, supervisor consultant, and contractor on the design-build project used as a case study. The results showed the top 10 factors influencing project communications with the highest Relative Importance Index value. The simple linear regression analysis result showed that project communications management has a positive and significant effect on project time performance with a coefficient of determination value of 69.6%. The suggested project communications management strategy is to optimize the application of the main factors of project communications, tailored to the result of the power/interest grid for each project stakeholder.